PENGARUH PANJANG AXIS EMBRIO TERHADAP PERTUMBUHAN BIBIT AREN (Arenga pinnata Merr) - Farida Farida (ZIRAA'AH MAJALAH ILMIAH PERTANIAN, 2018)
The effect of embryonic axis length on growth sugar palm seeds (Arenga pinnata Merr) was conducted to determine effect of embryonic axis length to vegetative growth palm seeds. This research obtained for three mounth on February to Mey 2017. The research was conducted in Kabo Street, Bum Taka, Swarga Bara Village Sangatta Sub-distrct East Kutai. This research uses is Completely Randomized Design (CRD) of non factorial experiments each of four treatment factorial (fourth) times such as Factor axis length (A) are : A1 = axis length 0 - 2 cm, A2 = axis length 2 - 4 cm, A3 = axis length 4 - 6 cm, A4 = axis length 6 - 8 cm, A5 = axis length 8 - 10 cm, A6 = axis length 10 - 12 cm. The research result to showed was (1) treatment axis length giving are effected significantly of increasing parameter embryonic axis length and plumula length. But to showing insignificant parameters were increasing parameter embryonic axis length, diameter of embryonic axis and plumula length sequent of 9,25 cm, 0,50 cm, and 5,50 cm.